Chemopreventive and therapeutic effects of Hippophae rhamnoides L. fruit peels evaluated in preclinical models of breast carcinoma - Dvorska, Dana; Sebova, Dominika; Kajo, Karol; Kapinova, Andrea; Svajdlenka, Emil; Goga, Michal; Frenak, Richard; Treml, Jakub; Mersakova, Sandra; Strnadel, Jan; Mazurakova, Alena; Baranova, Ivana; et al. (Frontiers in pharmacology, 2025)
BACKGROUND: Cancer remains a major global health challenge, necessitating innovative prevention and treatment approaches. Certain plants, adapted to specific environments, may exhibit bioactive properties with potential anticancer applications. HYPOTHESIS: Seaberry (Hippophae rhamnoides L.) fruit peels may exert anticancer effects in breast carcinoma (BC) models through the additive or synergistic actions of their unique secondary metabolites. METHODS: H. rhamnoides fruit peel extracts were analyzed using the LC-DAD-MS and LC-DAD techniques to profile the content of carotenoids and flavonoids, respectively. The preclinical study evaluated seaberry fruit peel extracts in BC models: (1) a syngeneic 4T1 mouse breast adenocarcinoma model (triple-negative), (2) a rat model of chemically induced mammary carcinogenesis, and (3) in vitro studies with MCF-7 (hormone receptor-positive) and MDA-MB-231 (triple-negative) BC cell lines. RESULTS: LC-DAD-MS and LC-DAD analyses identified dominant metabolites, including isorhamnetin, quercetin glycosides, kaempferol glycosides, catechin, zeaxanthin, and lutein. In the 4T1 mouse model, seaberry treatment resulted in a significant, dose-dependent reduction in tumor volume (43% and 48% compared to controls) and a decrease in the mitotic activity index. Serum cytokine analysis showed dose-dependent reductions in IL-6, IL-10, and TNF-α. In the rat chemopreventive model, high-dose seaberry improved cancer prognosis by reducing the ratio of poorly differentiated tumors and increasing caspase-3 and Bax expression while decreasing Ki-67 and malondialdehyde levels. Both treatment doses elevated the Bax/Bcl-2 ratio and reduced the expression of cancer stem cell markers CD44, EpCam, and VEGF compared to controls. Epigenetic analyses revealed histone modifications (H4K16ac, H4K20me3) and altered methylation of tumor-suppressor genes (PITX2, RASSF1, PTEN, TIMP3). Microarray analysis (758 miRNAs) identified beneficial changes in nine oncogenic/tumor-suppressive miRNAs, including miR-10a-5p, miR-322-5p, miR-450a-5p, miR-142-5p, miR-148b-3p, miR-1839-3p, miR-18a-5p, miR-1949, and miR-347. In vitro, ethanolic seaberry extract conferred partial resistance to cisplatin-induced cytotoxicity in MCF-7 and MDA-MB-231 cells at IC50 concentrations. CONCLUSION: This study of H. rhamnoides in rodent BC models shows promising data but requires rigorous, long-term validation. Integrating plant-based nutraceuticals into oncology necessitates precise cancer-type profiling and patient stratification for effective personalized treatments.
Keywords: chemoprevention; breast carcinoma; rodent models; epigenetics; Hyppophae rhamnoides L.; therapy modulation; cancer stem cells